On a moment problem associated with Chebyshev polynomials - Castillo, K.; Lamblem, R. L.; Ranga, Alagacone Sri [UNESP] (Elsevier B.V., 2012)
Given a sequence {mu(n)}(n-0)(infinity) of real numbers, we find necessary and sufficient conditions for the existence and uniqueness of a distribution function phi on (1, infinity), such thatmu(n) = integral(infinity)(1) T-n(x)d phi(x), n = 0, 1, 2, ...Here T-n(x) are the Chebyshev polynomials of the first kind. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Moment problem; Szego polynomials on the real line; Chebyshev polynomial; Hankel determinants